Energy optimization of pneumatic actuating systems using expansion energy and exhaust recycling. (1st May 2020) - Du, Hongwang; Hu, Chaochun; Xiong, Wei; Jiang, Zhong'ai; Wang, Lu
Abstract: As an important power source in industrial applications, compressed air makes up an increasingly large proportion of total industrial energy consumption. Due to the compression and leakage of air, however, pneumatic actuating systems have suffered from a low utilization of compressed air. Moreover, for a traditional pneumatic circuit, a three-position five-way valve is used to control the air inlet and exhaust with a single pressure, also causing low efficiency. This study proposes a novel bridge circuit to realize energy savings through utilizing compressed air expansion energy and exhaust energy. The circuit consisted of five two-position two-way switch valves. The open-and-close sequence of these valves was used to control the motions of a cylinder piston. This circuit could realize system energy conservation by less air intake and waste air reuse, while simultaneously ensuring that the piston reached the end of its stroke with stability. In order to optimize air consumption, a nonlinear dynamic system optimization model was built based on the idea of dynamic optimization, and the pressure and flow of the pneumatic system and the dynamic equation were considered as constraint conditions. Optimization of the open-and-close sequence of the five switch valves in the bridge circuit was conducted using orthogonal collocation on finite elements and the interior point method. Lastly, a bridge actuator test platform was built to test the stability and energy efficiency of the proposed pneumatic circuit based on the open-and-close sequence obtained through the optimization algorithm with different air supply pressures and workloads. Compared with the traditional circuit, the proposed circuit yielded energy savings of 55–87%, and the impact acceleration at the end point is smaller than that at the end point, with only −0.01–0.02 m/s. These results suggested that the circuit is important for enhancing the utilization of compressed air.